2023
DOI: 10.22373/sjhk.v7i1.14621
|View full text |Cite
|
Sign up to set email alerts
|

Juridical Provisions on Government Policies Towards Marginal Economic Actors in Indonesia in the Perspective of Islamic Law

Abstract: This study investigates the legal provisions for dealing with street vendors in Banda Aceh and Yogyakarta, utilizing the Qanun no. 3/2007 and the Mayor Regulation no. 26/2002, respectively. It investigates the variables that constitute the basis for the creation of policies for dealing with street sellers and evaluates policy formulations for dealing with street vendors in the two provincial capitals in a more accommodating and comprehensive manner. This is a normative legal research that examines legal data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, Voiculescu (2018) showed that diverse disciplines enable economic, political, and social policy development in network governance (Alidar et al, 2023). Fowler et al (2019) assessed the implementation of policies from changes to the homeless service system, where a supportive network governance structure is needed.…”
Section: Policy Sub-sectionmentioning
confidence: 99%
“…Therefore, Voiculescu (2018) showed that diverse disciplines enable economic, political, and social policy development in network governance (Alidar et al, 2023). Fowler et al (2019) assessed the implementation of policies from changes to the homeless service system, where a supportive network governance structure is needed.…”
Section: Policy Sub-sectionmentioning
confidence: 99%
“…Based on this, the Dumai City government has the potential to utilize companies to support government programs for the welfare of the local community as a positive impact from the presence of relatively many companies. Still, on the other hand, the community will also feel the adverse effects of various corporate activities, such as environmental pollution and massive exploitation of energy consumption and natural resources, which harm the environment in the region (Afrino et al, 2023;Setiawan, 2021;Yuslaini et al, 2023;Alidar et al, 2023).…”
Section: A Introductionmentioning
confidence: 99%
“…On the other hand, this duty has two dimensions: horizontal, referring to the authority to structure government properly, and vertical, referring to the duty itself. Autonomous regions also regulate and manage central matters, while the central government retains supervisory powers over these regions (Alidar et al, 2023). Therefore, the unitary framework embodies the central government's authority to intervene more intensively in regional matters.…”
Section: A Introductionmentioning
confidence: 99%